Conditions simulating androgenetic alopecia. (8th January 2015) - Rossi, A.; Iorio, A.; Di Nunno, D.; Priolo, L.; Fortuna, M.C.; Garelli, V.; Carlesimo, M.; Calvieri, S.; Mari, E.
Abstract Androgenetic alopecia is a common form of hair loss, characterized by a progressive hair follicular miniaturization, caused by androgen hormones on a genetically susceptible hair follicle, in androgenic‐dependent areas. Characteristic phenotype of androgenetic alopecia is also observed in many other hair disorders. These disorders are androgenetic‐like diseases that cause many differential diagnosis or therapeutic error problems. The objective of this review was to systematically analyse the greatest number of conditions that mimic the AGA pattern and explain their disease pathogenesis.